2021
DOI: 10.3390/su132413998
|View full text |Cite
|
Sign up to set email alerts
|

Use of Wearable Devices to Study Physical Activity in Early Childhood Education

Abstract: Physical activity recommendations for early childhood are gradually being met to a lesser extent today. The objectives of the study were: (i) to assess the degree of compliance with physical activity (PA) recommendations by gender; and (ii) to analyze the level of PA and steps in different periods over a week. This study was an observational cross-sectional study. Sixty-three young children (33 boys and 30 girls) aged two years (2.15 ± 0.35) were recruited for this study. Participants wore a “Garmin vivofit® j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…With respect to World Health Organization recommendations (WHO, 2019) that children under three years old should have at least 180 minutes of PA of any intensity every day, Vega-Perona et al (2022) and Díaz-Quesada et al (2021) also found that daycare facilities were positive environments for achieving these PA recommendations for 2-year olds in Spain. As toddlers spend an average of 7 hours a day in preschool and daycare, outdoor time during school hours is a good opportunity for achieving their recommended PA levels.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to World Health Organization recommendations (WHO, 2019) that children under three years old should have at least 180 minutes of PA of any intensity every day, Vega-Perona et al (2022) and Díaz-Quesada et al (2021) also found that daycare facilities were positive environments for achieving these PA recommendations for 2-year olds in Spain. As toddlers spend an average of 7 hours a day in preschool and daycare, outdoor time during school hours is a good opportunity for achieving their recommended PA levels.…”
Section: Discussionmentioning
confidence: 99%
“…To compare groups, a series of inferential statistical tests was performed. The t-test was then computed for independent samples to compare gender (boys vs. girls), In addition, the Student's paired samples t-test was employed to examine the differences between various moments (midweek vs. weekend and school time vs. out-of-school time), in line with previous similar studies [19,30]. A p-value of less than 0.05 was deemed statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, WDs have increased in popularity due to their fashionable and affordable nature, and when used properly, they can change their lifestyle habits. Although the technology has existed for some time in devices such as smart phones, WDs are ideal for monitoring PA in school children because of their portability [30]. Their ability to collect data quickly and efficiently has contributed to their widespread use in the scientific literature [31,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It serves a single purpose, is primarily market-oriented, and is solely motivated by profit. Among other things, there is less effective public service information, less transparency, less sharing of information resources, an inadequate supply of effective resources, public service functions have not been accurately reflected, and service quality must be improved [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%